Graphene protective film and preparation method thereof

By preparing graphene protective films and using emulsified adhesives with specific polymeric monomers and initiators, the contradiction of performance requirements of existing surface protective films in the consumer electronics market is solved, and efficient bonding, peeling and aging resistance is achieved.

CN119391315AInactive Publication Date: 2025-02-07YIXING WANGZHE LAMINATING FILM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510006362.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing surface protective films have performance requirements such as low peel strength, high light transmittance, low haze, excellent heat and heat resistance in the consumer electronics market, but it is difficult to meet these requirements at the same time.

Method used

Using the preparation method of graphene protective film, by mixing emulsifier and deionized water as emulsification solvent, acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, tert-butyl 2-(trifluorometh)acrylate, modified Polymer monomers such as acrylate and ammonium persulfate as an initiator, emulsified adhesive is prepared for preparing graphene protective films with tempered glass and PET as materials.

Benefits of technology

It achieves good adhesion of graphene protective film, easy peeling, no residual glue, good exhaust effect, easy sticking, no snowflake phenomenon, high light transmittance, and low haze, meeting the comprehensive performance needs of the consumer electronics market.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of surface protection films, and particularly discloses a graphene protection film and a preparation method thereof. The graphene protective film comprises a PET (Polyethylene Terephthalate) film, toughened glass and a release film are respectively adhered to two side surfaces of the PET film; the PET film and the toughened glass as well as the PET film and the release film are adhered through an adhesive; the adhesive comprises the following components: a mixed emulsifier, acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, 2-(trifluoromethyl) tert-butyl acrylate, modified acrylate and deionized water. The graphene protective film prepared by the invention has the advantages of good cohesiveness, easiness in stripping, no adhesive residue, good exhaust performance, easiness in adhesion, no snowflake phenomenon, high light transmittance and low haze.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of surface protection films, and more specifically, to a graphene protection film and a preparation method thereof. Background Art

[0002] Surface protection film is a special film material that has a protective function on the surface of other materials. It is widely pasted on the surface of various high-finish materials such as stainless steel plates, organic glass, plastic plates, electronic products, etc., to prevent the surface from being scratched, worn and contaminated during transportation, processing, storage and use. A high-quality surface protection film, in addition to having no bad smell, must also be easy to stick and peel on the specific surface of the protected material without any pollution. The basic structure of the surface protection film includes an adhesive layer and a substrate layer.

[0003] According to the different dispersion media, adhesives can be divided into water-soluble adhesives, solvent-based adhesives, emulsion adhesives, hot-melt adhesives, calendering adhesives, etc. Among them, water-soluble adhesives are widely used.

[0004] Different usage scenarios require different performance requirements for water-based adhesives: adhesive materials with a short usage time need to have a low residual adhesive rate; adhesives with a long usage time need to be resistant to yellowing; when the bonded substrate is a non-polar material, the adhesive needs to have high leveling properties; in environments with high humidity, the adhesive needs to have high water resistance, etc. The protective films used in the consumer electronics market usually require low peel strength, high light transmittance, low haze, and excellent heat and humidity resistance. Summary of the invention

[0005] In order to further improve the comprehensive performance of surface protection films in the consumer electronics market, the present application provides a graphene protection film and a preparation method thereof.

[0006] In a first aspect, the present application provides a graphene protective film, which adopts the following technical solution: A method for preparing a graphene protective film comprises a PET film; one side of the PET film is a glass side surface and is laminated with a tempered glass; the other side of the PET film is a machine side surface and is laminated with a release film; the PET film and the tempered glass, and the PET film and the release film are laminated with an adhesive; the components of the adhesive include a mixed emulsifier, acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, tert-butyl 2-(trifluoromethyl)acrylate, modified acrylate and deionized water.

[0007] By adopting the above technical scheme, a mixed emulsifier and deionized water are used as emulsifying solvents, acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, 2-(trifluoromethyl) tert-butyl acrylate, and modified acrylate are used as polymerization monomers, and ammonium persulfate is used as an initiator to prepare an emulsified adhesive, which is used for preparing a graphene protective film with tempered glass and PET as materials. The emulsified adhesive has good adhesion, is easy to peel off, has no residual glue, has a good exhaust effect, is easy to paste, has no snowflake phenomenon, has high light transmittance, and has low haze.

[0008] Preferably, the preparation method of the adhesive is as follows: S1, mixing and stirring a mixed emulsifier, sodium bicarbonate and deionized water to obtain a pre-emulsion solvent, then taking 85-90% of the volume of the pre-emulsion solvent, adding a polymerization monomer, and stirring at a speed of 300-400r / min for 30-50min to obtain a pre-emulsion; S2, taking 3-8wt% of the pre-emulsion in S1 and the remaining volume of the emulsifier and the pre-emulsion solvent, mixing them evenly at a speed of 200-250r / min, heating to 75-80°C, and then adding 25-30% of the mass of the initiator. After 10-15min, slowly dripping the remaining pre-emulsion and initiator, and continuing the reaction at this temperature for 1.5-2h to obtain a reaction solution; S3, cooling the reaction solution to 38-42°C, dripping ammonia water to adjust the pH of the reaction solution to 7.2-7.8, filtering, collecting the filtrate, and obtaining the adhesive.

[0009] By adopting the above technical scheme, acrylic acid and hydroxyethyl acrylate are used as stabilizing functional monomers and a specific proportion of SR-10 and BES-20 mixed emulsifiers are used to increase the stability of the adhesive emulsion, 2-(trifluoromethyl) tert-butyl acrylate is used to improve its hydrophobic and oleophobic properties and cohesive force, glycidyl methacrylate is used as a self-crosslinking functional monomer to increase the cohesive force of the adhesive and improve the stickiness, and modified acrylate obtained by esterifying 3-(acryloyloxy)-2-hydroxypropyl methacrylate with carboxylated graphene is used as a functional monomer, and a crosslinking reaction is carried out under the action of a photoinitiator to improve the initial viscosity, and the aging resistance is improved by increasing the overall crosslinking density; the finally prepared adhesive has strong stability, suitable adhesion and peeling strength, and good aging resistance and water resistance.

[0010] Preferably, the polymerizable monomers are acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, tert-butyl 2-(trifluoromethyl)acrylate, and modified acrylic acid ester, and the added mass ratio thereof is 20-25:15-18:8-10:12-15:5-8.

[0011] By adopting the above technical solutions, the comprehensive performance of the graphene protective film is optimal.

[0012] Preferably, the mixed emulsifier is a mixture of SR-10 and BES-20 in a mass ratio of 2:1.

[0013] By adopting the above technical solution, the adhesive emulsion has the best stability.

[0014] Preferably, the mass volume ratio of the mixed emulsifier, sodium bicarbonate and deionized water is (5-7) g: (0.5-0.8) g: (50-80) mL.

[0015] Preferably, the mass content of the mixed emulsifier is 3-5% of the total mass of the polymerized monomers.

[0016] By adopting the above technical solutions, the stability, viscosity and adhesion of the adhesive are optimally balanced.

[0017] Preferably, the initiator is ammonium persulfate, and the added amount of the initiator is 0.3-0.5wt% of the total mass of the polymerization monomers.

[0018] By adopting the above technical solution, the initiator with this content is added through the initial feeding and continuous dripping, the monomer conversion rate is high, the polymerization reaction process is stable, and the adhesive has excellent bonding performance.

[0019] Preferably, the preparation method of the modified acrylate is as follows: at 0°C, 3-(acryloyloxy)-2-hydroxypropyl methacrylate, DMAP (4-dimethylaminopyridine) and DCC (N,N'-dicyclohexylcarbodiimide) are added to a suspension of carboxylated graphene in sequence, stirred for 5-8 hours, then filtered, washed with dichloromethane 3-5 times, and vacuum dried at 70°C overnight to obtain the modified acrylate.

[0020] By adopting the above technical solution, the modified acrylic ester graphene obtained is evenly dispersed, which is beneficial to the stability of the adhesive.

[0021] Preferably, the mass volume ratio of the suspension of 3-(acryloyloxy)-2-hydroxypropyl methacrylate, DMAP and DCC, and carboxylated graphene is (15-20) g: (0.1-0.2) g: (2-3) g: (200-350) mL; the suspension of carboxylated graphene is prepared by uniformly dispersing 10 g of carboxylated graphene in 200-350 mL of DMF (N,N-dimethylformamide).

[0022] By adopting the above technical solution, the modification effect is the best.

[0023] In a second aspect, the present application provides a method for preparing a graphene protective film. A method for preparing a graphene protective film comprises the following steps: (1) subjecting both sides of a PET film to corona treatment with a corona machine to obtain a PET substrate; (2) coating an adhesive on both sides of the PET substrate, drying the glass side at a gradient temperature of 75-105° C., and drying the machine side at a gradient temperature of 80-100° C.; (3) attaching a tempered glass to the glass side and attaching a release film to the machine side to obtain a graphene protective film.

[0024] Preferably, the glass side is dried according to a program gradient heating of 75°C for 100 s, 88°C for 90 s, 95°C for 90 s, and 105°C for 80 s; the machine side is dried according to a program gradient heating of 80°C for 90 s, 85°C for 100 s, 95°C for 100 s, and 100°C for 90 s.

[0025] By adopting the above technical solution, the adhesion between the tempered glass and the PET substrate is improved, and the graphene protective film is easy to peel off.

[0026] In summary, this application has the following beneficial effects: 1. The present application uses a mixed emulsifier and deionized water as emulsifying solvents, acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, tert-butyl 2-(trifluoromethyl)acrylate, and modified acrylate as polymerization monomers, and ammonium persulfate as an initiator to prepare an emulsified adhesive for preparing a graphene protective film with tempered glass and PET as the substrate, and has excellent comprehensive performance.

[0027] 2. In the present application, acrylic acid and hydroxyethyl acrylate are preferably used as stabilizing functional monomers in combination with a specific ratio of SR-10 and BES-20 mixed emulsifiers to increase the stability of the adhesive emulsion, 2-(trifluoromethyl) tert-butyl acrylate is used to improve its hydrophobic properties and polymerization density, glycidyl methacrylate is used as a self-crosslinking functional monomer to increase the cohesion of the adhesive and improve the stickiness, and modified acrylate obtained by esterifying 3-(acryloyloxy)-2-hydroxypropyl methacrylate with carboxylated graphene is used as a functional monomer. Under the action of a photoinitiator, a crosslinking reaction is performed to improve the initial viscosity, and the aging resistance is improved by increasing the overall crosslinking density; the finally prepared adhesive has strong stability, suitable adhesion and peel strength, and good aging resistance and water resistance.

[0028] 3. The graphene protective film prepared by the preparation method of the present application has good adhesion, is easy to peel off, has no residual glue, has good exhaust performance, is easy to paste, has no snowflake phenomenon, has high light transmittance and low haze. DETAILED DESCRIPTION

[0029] The present application is further described in detail below with reference to the embodiments.

[0030] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0031] Example Example 1 A graphene protective film is prepared by the following method: (1) treating both sides of a PET film with a corona machine to obtain a PET substrate; (2) coating an adhesive on both sides of the PET substrate, drying the glass side according to a programmed gradient heating of 75°C for 100 s, 88°C for 90 s, 95°C for 90 s, and 105°C for 80 s, and drying the machine side according to a programmed gradient heating of 80°C for 90 s, 85°C for 100 s, 95°C for 100 s, and 100°C for 90 s; (3) laminating a tempered glass on the glass side and a release film on the machine side to obtain a graphene protective film.

[0032] The coating thickness of the glass side adhesive is 35µm, and the coating thickness of the machine side adhesive is 25µm.

[0033] PET film was purchased from Dongguan Zhonglian Electronic Materials Co., Ltd.

[0034] The release film may be made of PET, PE, PP, TPU or PVB.

[0035] The preparation method of the adhesive is as follows: S1, mixing and stirring a mixed emulsifier, sodium bicarbonate and deionized water to obtain a pre-emulsion solvent, then taking 85% volume of the pre-emulsion solvent, adding a polymerization monomer, and stirring at a speed of 300 r / min for 30 minutes to obtain a pre-emulsion; The polymerizable monomers are acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, tert-butyl 2-(trifluoromethyl)acrylate, and modified acrylate, and the added mass ratio thereof is 20:15:8:12:5; The mixed emulsifier is a mixture of SR-10 and BES-20 in a mass ratio of 2:1; The mass volume ratio of the mixed emulsifier, sodium bicarbonate and deionized water is 5g:0.5g:50mL; S2, take 3wt% of the pre-emulsion in S1 and mix with the remaining volume of emulsifier and pre-emulsion solvent, stir evenly at a speed of 200r / min, heat to 75°C, then add 25% by weight of initiator, after 10 minutes, slowly dropwise add the remaining pre-emulsion and initiator, continue to react at this temperature for 1.5h, and obtain a reaction solution; The initiator is ammonium persulfate, and the amount of the initiator added is 0.3wt% of the total mass of the polymerization monomers; S3, cooling the reaction solution to 38° C., adding ammonia water dropwise to adjust the pH of the reaction solution to 7.2, filtering, and collecting the filtrate to obtain an adhesive.

[0036] The preparation method of the modified acrylate is as follows: at 0°C, 3-(acryloyloxy)-2-hydroxypropyl methacrylate, DMAP and DCC are sequentially added to a suspension of carboxylated graphene, stirred for 5 hours, then filtered, washed with dichloromethane 3 times, and vacuum dried overnight at 70°C to obtain the modified acrylate; the mass volume ratio of the suspension of 3-(acryloyloxy)-2-hydroxypropyl methacrylate, DMAP and DCC, and carboxylated graphene is 15g:0.1g:2g:200mL; the suspension of carboxylated graphene is prepared by uniformly dispersing 10g of carboxylated graphene in 200mL of DMF; carboxylated graphene is purchased from Nanjing Jicang Nano Technology Co., Ltd., with a sheet diameter of 50-200nm and a thickness of 0.8-1.2nm.

[0037] 20.0 mg of adhesive was drawn into a test tube, and then the residual monomer in the adhesive was determined using a gas chromatograph. The residual amount of each monomer in the adhesive, Mi, was obtained through the supporting software. Then the total monomer conversion rate was calculated. The total monomer conversion rate T = 1-∑ (Mi) / 1000m, Mi = the residual amount of a single monomer, mg / kg; m = the mass of the monomer in the adhesive, g / kg. The result showed that the total monomer conversion rate reached 91.5%. This shows that the overall reaction of the polymerization monomer is good.

[0038] The glass transition temperature of the adhesive was measured by differential scanning calorimetry to be -46.0°C. The adhesive with this glass transition temperature had a better balance between initial adhesion and sustained adhesion.

[0039] Example 2 A graphene protective film is prepared by the following method: (1) treating both sides of a PET film with a corona machine to obtain a PET substrate; (2) coating an adhesive on both sides of the PET substrate, drying the glass side according to a programmed gradient heating of 75°C for 100 s, 88°C for 90 s, 95°C for 90 s, and 105°C for 80 s, and drying the machine side according to a programmed gradient heating of 80°C for 90 s, 85°C for 100 s, 95°C for 100 s, and 100°C for 90 s; (3) laminating a tempered glass on the glass side and a release film on the machine side to obtain a graphene protective film.

[0040] The coating thickness of the glass side adhesive is 35µm, and the coating thickness of the machine side adhesive is 25µm.

[0041] The preparation method of the adhesive is as follows: S1, mixing and stirring a mixed emulsifier, sodium bicarbonate and deionized water to obtain a pre-emulsion solvent, then taking 88% volume of the pre-emulsion solvent, adding a polymerization monomer, and stirring at a speed of 350 r / min for 40 min to obtain a pre-emulsion; The polymerizable monomers are acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, tert-butyl 2-(trifluoromethyl)acrylate, and modified acrylate, and the added mass ratio thereof is 22:17:9:14:7; The mixed emulsifier is a mixture of SR-10 and BES-20 in a mass ratio of 2:1; The mass volume ratio of the mixed emulsifier, sodium bicarbonate and deionized water is 6g:0.7g:65mL; S2, take 5wt% of the pre-emulsion in S1 and mix with the remaining volume of emulsifier and pre-emulsion solvent, stir evenly at a speed of 230r / min, heat to 78°C, then add 25-30% by weight of initiator, after 13 minutes, slowly dropwise add the remaining pre-emulsion and initiator, continue to react at this temperature for 2 hours, and obtain a reaction solution; The initiator is ammonium persulfate, and the amount of the initiator added is 0.4wt% of the total mass of the polymerization monomers; S3, cooling the reaction solution to 40°C, adding ammonia water to adjust the pH of the reaction solution to 7.5, filtering, and collecting the filtrate to obtain an adhesive.

[0042] The preparation method of the modified acrylate is as follows: at 0°C, 3-(acryloyloxy)-2-hydroxypropyl methacrylate, DMAP and DCC are sequentially added to a suspension of carboxylated graphene, stirred for 6.5 hours, then filtered, washed with dichloromethane 4 times, and vacuum dried overnight at 70°C to obtain the modified acrylate; the mass volume ratio of the suspension of 3-(acryloyloxy)-2-hydroxypropyl methacrylate, DMAP and DCC, and carboxylated graphene is 18g:0.15g:2.5g:280mL; the suspension of carboxylated graphene is prepared by uniformly dispersing 10g of carboxylated graphene in 280mL of DMF; the carboxylated graphene is purchased from Nanjing Jicang Nano Technology Co., Ltd., with a sheet diameter of 1-5µm and a thickness of 0.8-1.2nm.

[0043] Example 3 A graphene protective film is prepared by the following method: (1) treating both sides of a PET film with a corona machine to obtain a PET substrate; (2) coating an adhesive on both sides of the PET substrate, drying the glass side according to a programmed gradient heating of 75°C for 100 s, 88°C for 90 s, 95°C for 90 s, and 105°C for 80 s, and drying the machine side according to a programmed gradient heating of 80°C for 90 s, 85°C for 100 s, 95°C for 100 s, and 100°C for 90 s; and (3) laminating a tempered glass on the glass side and a release film on the machine side to obtain a graphene protective film.

[0044] The coating thickness of the glass side adhesive is 35µm, and the coating thickness of the machine side adhesive is 25µm.

[0045] The preparation method of the adhesive is as follows: S1, mixing and stirring a mixed emulsifier, sodium bicarbonate and deionized water to obtain a pre-emulsion solvent, then taking 90% of the volume of the pre-emulsion solvent, adding a polymerization monomer, and stirring at a speed of 400 r / min for 50 minutes to obtain a pre-emulsion; The polymerizable monomers are acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, tert-butyl 2-(trifluoromethyl)acrylate, and modified acrylate, and the added mass ratio thereof is 25:18:10:15:8; The mixed emulsifier is a mixture of SR-10 and BES-20 in a mass ratio of 2:1; The mass volume ratio of the mixed emulsifier, sodium bicarbonate and deionized water is 7g:0.8g:80mL; S2, take 8wt% of the pre-emulsion in S1 and mix with the remaining volume of emulsifier and pre-emulsion solvent, stir evenly at a speed of 250r / min, heat to 80°C, then add 30% by weight of initiator, after 15 minutes, slowly dropwise add the remaining pre-emulsion and initiator, continue to react at this temperature for 2 hours, and obtain a reaction solution; The initiator is ammonium persulfate, and the amount of the initiator added is 0.5wt% of the total mass of the polymerization monomers; S3, cooling the reaction solution to 42° C., dropping ammonia water to adjust the pH of the reaction solution to 7.8, filtering, and collecting the filtrate to obtain an adhesive.

[0046] The preparation method of the modified acrylate is as follows: at 0°C, 3-(acryloyloxy)-2-hydroxypropyl methacrylate, DMAP and DCC are sequentially added to a suspension of carboxylated graphene, stirred for 5-8h, then filtered, washed with dichloromethane 5 times, and vacuum dried overnight at 70°C to obtain the modified acrylate; the mass volume ratio of the suspension of 3-(acryloyloxy)-2-hydroxypropyl methacrylate, DMAP and DCC, and carboxylated graphene is 20g:0.2g:3g:350mL; the suspension of carboxylated graphene is prepared by uniformly dispersing 10g of carboxylated graphene in 350mL of DMF; the carboxylated graphene is purchased from Nanjing Jicang Nano Technology Co., Ltd., with a sheet diameter of 1-5µm and a thickness of 0.8-1.2nm.

[0047] Comparative Example Comparative Example 1 The same as Example 2, except that the polymerizable monomer does not contain modified acrylate, and the total amount of polymerizable monomer added remains unchanged.

[0048] Comparative Example 2 The same as Example 2, except that "tert-butyl 2-(trifluoromethyl)acrylate" is replaced with an equal mass of "butyl methacrylate".

[0049] Comparative Example 3 The same as Example 2, except that the mixing ratio of SR-10 and BES-20 in the mixed emulsifier is adjusted to a mass ratio of 1:1.

[0050] Performance testing The adhesives prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to the following tests: (1) Stability test: Take 20 mL of adhesive in a centrifuge tube and centrifuge the tube at 4000 r / min for 40 min. Observe whether the adhesive shows stratification or demulsification after centrifugation.

[0051] (2) Take 0.5 mL of adhesive and dilute it with 800 mL of deionized water. After ultrasonic oscillation for 30 minutes, use a particle size analyzer to test its average particle size and distribution.

[0052] (3) Adhesion test: Initial adhesion test is based on GB / T31125-2014 method; sustained adhesion test is based on GB / T4851-1998 method; 180° peel strength test is based on GB / T2792-2014 method.

[0053] (4) High temperature and high humidity resistance test: Place the product in a constant temperature and humidity aging box at 70°C and 95% humidity for 72 hours, and then test the adhesion and 180° peel strength of the aged product.

[0054] (5) Water absorption test: Cut a piece of film of about 3 cm × 3 cm, weigh it as M, soak it in water at room temperature for 24 h, take it out and quickly wipe off the surface moisture with a paper towel, weigh it as m, water absorption (%) = (mM) / M×100.

[0055] (6) Water whitening recovery test: 3 mL of adhesive is applied to a glass plate to form a thin film, and then placed in a constant temperature and humidity environment to form a film and cured for 24 hours. Then, the glass plate is placed in a water tank and taken out after soaking for 24 hours. The light transmittance of the film is measured every 20 minutes using a haze tester until the film is completely restored to colorless and transparent state, and the time required for the final recovery is recorded.

[0056] The results are shown in Table 1: Table 1. Adhesive performance test

[0057] As can be seen from Table 1, the adhesives prepared in Examples 1-3 of the present application have excellent comprehensive performance, strong stability, suitable adhesion and peeling strength, and good aging resistance and water resistance.

[0058] The graphene protective films prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to residual adhesive performance tests according to the "Q_Ali00006-2017 Technical Specifications for Mobile Phone Protective Films", and the transmittance and haze were tested according to the ASTMD1003 method. The exhaust performance test: in a dust-free environment, the release film was torn off and attached to a glass plate to observe the adhesive effect; after attachment, observe whether there are snowflakes that cannot be eliminated. The results are shown in Table 2: Table 2. Protective film performance test

[0059] It can be seen from Table 2 that the homemade adhesive graphene protective film used in this application has good adhesion, is easy to peel off, has no residual glue, has a good exhaust effect, is easy to paste, has no snowflake phenomenon, has high light transmittance and low haze.

[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.

Claims

1. A graphene protective film, characterized in that: The invention comprises a PET film; one side of the PET film is a glass side surface, on which a tempered glass is bonded; the other side of the PET film is a machine side surface, on which a release film is bonded; the PET film and the tempered glass, and the PET film and the release film are bonded by an adhesive; the components of the adhesive include a mixed emulsifier, acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, tert-butyl 2-(trifluoromethyl)acrylate, modified acrylate and deionized water; the preparation method of the adhesive is as follows: S1, mixing and stirring the mixed emulsifier, sodium bicarbonate and deionized water to obtain a pre-emulsion solvent, then taking 85-90% by volume of the pre-emulsion solvent, adding a polymerization monomer, and mixing at 3 00-400r / min and stir for 30-50min to obtain a pre-emulsion; S2, take 3-8wt% of the pre-emulsion in S1 and mix with the remaining volume of the emulsifier and the pre-emulsion solvent, stir evenly at a speed of 200-250r / min, heat to 75-80℃, and then add 25-30% by weight of the initiator. After 10-15min, slowly drop the remaining pre-emulsion and initiator, and continue to react at this temperature for 1.5-2h to obtain a reaction solution; S3, cool the reaction solution to 38-42℃, add ammonia water to adjust the pH of the reaction solution to 7.2-7.8, filter, collect the filtrate, and obtain the adhesive.

2. A graphene protective film according to claim 1, characterized in that: The polymerizable monomers are acrylic acid, hydroxyethyl acrylate, glycidyl methacrylate, tert-butyl 2-(trifluoromethyl)acrylate, and modified acrylic acid ester, and the added mass ratio thereof is 20-25:15-18:8-10:12-15:5-8.

3. A graphene protective film according to claim 2, characterized in that: The mixed emulsifier is a mixture of SR-10 and BES-20 in a mass ratio of 2:

1.

4. A graphene protective film according to claim 3, characterized in that: The mass volume ratio of the mixed emulsifier, sodium bicarbonate and deionized water is (5-7) g: (0.5-0.8) g: (50-80) mL.

5. A graphene protective film according to claim 4, characterized in that: The mass content of the mixed emulsifier is 3-5% of the total mass of the polymerized monomers.

6. A graphene protective film according to claim 5, characterized in that: The initiator is ammonium persulfate, and the added amount of the initiator is 0.3-0.5wt% of the total mass of the polymerization monomers.

7. A graphene protective film according to claim 6, characterized in that: The preparation method of the modified acrylate is as follows: at 0°C, 3-(acryloyloxy)-2-hydroxypropyl methacrylate, DMAP and DCC are sequentially added to a suspension of carboxylated graphene, stirred for 5-8 hours, then filtered, washed with dichloromethane for 3-5 times, and vacuum dried overnight at 70°C to obtain the modified acrylate; the mass volume ratio of the suspension of 3-(acryloyloxy)-2-hydroxypropyl methacrylate, DMAP and DCC, and carboxylated graphene is (15-20) g: (0.1-0.2) g: (2-3) g: (200-350) mL; the suspension of carboxylated graphene is prepared by uniformly dispersing 10 g of carboxylated graphene in 200-350 mL of DMF.

8. A method for preparing a graphene protective film according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: (1) subjecting both sides of a PET film to corona treatment by a corona machine to obtain a PET substrate; (2) coating an adhesive on both sides of the PET substrate, drying the glass side at a gradient temperature of 75-105° C., and drying the machine side at a gradient temperature of 80-100° C.; (3) laminating a tempered glass on the glass side and a release film on the machine side to obtain a graphene protective film.

9. The method for preparing a graphene protective film according to claim 8, characterized in that: The glass side was dried according to the program gradient heating: 75°C for 100s, 88°C for 90s, 95°C for 90s, and 105°C for 80s; the machine side was dried according to the program gradient heating: 80°C for 90s, 85°C for 100s, 95°C for 100s, and 100°C for 90s.

Citation Information

Patent Citations

  • Water-blush-resistant fluoride and siloxane modified waterborne pressure-sensitive adhesive and polyethylene protective film

    CN102504733A

  • Graphene modified acrylic ester antistatic film and preparation method thereof

    CN106497301A

  • Method for synthesizing polymer material graphene through free radical polymerization

    CN110483668A

  • Preparation method of acrylate emulsion pressure-sensitive adhesive

    CN111849364A

  • Water-based fluorinated acrylate copolymer emulsion and preparation method thereof

    CN114656856A